INSTITUTIONAL RECLASSIFICATION AND FOREST RECOVERY TRAJECTORIES IN A TROPICAL PROTECTED AREA: EVIDENCE FROM GUNUNG HALIMUN SALAK NATIONAL PARK INDONESIA - Sulung Wahyu Widodo; Omo Rusdiana; Baba Barus (RADJA PUBLIKA, 2026)
Protected areas are widely recognized as key instruments for biodiversity conservation and forest protection; however, the long-term ecological outcomes of institutional changes in protected area management remain insufficiently understood. This study evaluated land-cover dynamics in Gunung Halimun Salak National Park (TNGHS), Indonesia, following major institutional transformations associated with park expansion and boundary reclassification. Land-cover datasets for 2003, 2009, 2014, 2019, and 2024 obtained from the Indonesian Ministry of Forestry were analyzed using Geographic Information Systems (GIS), transition matrices, and intensity analysis. Land-cover transitions were decomposed into persistence, gains, losses, net change, and swap components to identify underlying landscape dynamics beyond conventional net-change assessments. The results revealed a positive long-term trajectory of forest recovery. Forest cover increased from 67,100 ha (76.5%) in 2003 to 73,078 ha (83.3%) in 2024, resulting in a net forest gain of approximately 5,978 ha. Secondary forest exhibited the largest expansion, largely through transitions from plantation forests and agricultural land. Transition analysis indicated that forest gains (9,113 ha) substantially exceeded forest losses (3,135 ha). However, a considerable swap component (6,270 ha) demonstrated that forest recovery and forest loss occurred simultaneously in different locations, indicating ongoing spatial redistribution of land-cover change within the park. These findings suggest that institutional reclassification and conservation-oriented management have contributed to forest recovery in TNGHS, supporting the Forest Transition Theory and evidence on protected area effectiveness. The study demonstrates that transition-based approaches provide a more comprehensive assessment of conservation outcomes than net-change statistics alone and underscores the importance of governance capacity, tenure certainty, and long-term monitoring in sustaining forest recovery within tropical protected areas